دور الاجتهاد المقاصدي وتطبيقه في فتوى مجلس العلماء الإندونيسي بشأن أداء العبادات خلال جائحة كوفيد - 19: THE ROLE OF IJTIHĀD MAQĀṢIDĪ AND ITS IMPLEMENTATION IN THE FATWA OF INDONESIAN ULAMA COUNCIL ON WORSHIP GUIDE AMID COVID-19 PANDEMIC (International Seminar on Syariah and Law (INSLA), 2020)
The spread of the covid-19 virus outbreak has caused various problems in human life, both from economic, social, political and religious aspects. The Indonesian Ulama Council (MUI), which is the official institution of the Indonesian state in terms of religious fatwas, has a very important role in dealing with the problem of the Covid-19, namely by providing religious guidelines, directions or fatwas in order to reduce and prevent the spread of a very dangerous virus. this. So, this study aims to try to analyze the fatwa of the Indonesian Ulama Council on worship guidelines during the Covid-19 pandemic with the ijtihād maqāṣidī (maqāṣhid sharia) approach which is also one of the methods or approaches used by the Indonesian Ulama Council. This research also tries to reconstruct the maqāṣhid sharia hierarchy (hifdz ad-dīn, nafs, māl, ‘aql, nasl) to obtain the ideal concept, especially if there is a conflict between one another. This research is an inductive qualitative research where the data collection is done by using documentation method, then the data is analyzed using descriptive analytic method.  أدى انتشار الفيروس الخطير المسمى بــــــ "كوفيد -19" إلى العديد من المشاكل في الحياة البشرية، سواء كانت اقتصادية أو اجتماعية أو سياسية أو دينية، ولقد قام مجلس العلماء الإندونيسي - بصفته المؤسسة الرسمية للإفتاء - بدور هام في مواجهة انتشار الوباء "كوفيد – 19" بإصداره الفتوى خلال هذه الجائحة من أجل التخفيف من انتشارها، فهذه الدراسة تهدف إلى تحليل مدى استخدام مجلس العلماء الإندونيسي نظرية الاجتهاد المقاصدي وأهميته في الإفتاء وخاصة فيما يتعلق بتنفيذ العبادات خلال هذه الجائحة. ويتم تشجيع الباحث أيضًا على التوسع في البناء الهرمي لمقاصد الشريعة من أجل إيجاد المفهوم المثالي لأصول الخمسة (حفظ الدين، والنفس، والمال، والعقل، والنسل) لا سيما عندما حدث التعارض بين هذه الأصول الخمسة. هذا البحث هو البحث النوعي الاستقرائي بحيث يتم جمع البيانات بطريقة التوثيق، ثم يتم تحليل البيانات باستخدام الطريقة الوصفية التحليلي